Kissing Stents for Treatment of Aortoiliac Disease - Hossain, GM Mokbul; Mandal, Naresh Chandra; Dey, Nirmal Kanti; Mamun, Abdullah Al; Rahman, Motiur; Hasan, Rakibul (Bangladesh Heart Journal, 2016)
Objectives: To determine technical and clinical success of kissing stents for aortoiliac occlusive disease. Design: Retrospective study. Venue: Different private centers in Dhaka City. Subjects: Patients presenting with intermittent claudication (IC) or critical limb ischaemia (CLI) due to aortoiliac disease. Methods: Balloon or self expanding kissing stents with or without predilatation depending upon the nature of the disease, was inserted via bilateral retrograde femoral approach. Patients were followed up clinically and by ankle brachial index (ABI) and Duplex study. Results: Technical and clinical success was achieved in all of 34 cases. All patients with CLI improved and ulcerated limbs showed complete healing. During follow-up 3 patients died and 1 patient required major amputation at 3 months. Conclusion: Kissing stents implantation is a safe and alternative treatment for aortoiliac disease. It is cosmetic, requires short hospital stay. No incision, regional or general anesthesia is needed. Bangladesh Heart Journal 2015; 30(2) : 74-77